Regulation of the Anti-Inflammatory Cytokines Interleukin-4 and Interleukin-10 during Pregnancy - Chatterjee, Piyali; Chiasson, Valorie L.; Bounds, Kelsey R.; Mitchell, Brett M. (Frontiers in Immunology, 2014)
Inflammation mediated by both innate and adaptive immune cells is necessary for several important processes during pregnancy. Pro-inflammatory immune cell activation plays a critical role in embryo implantation, placentation, and parturition; however dysregulation of these cells can lead to detrimental pregnancy outcomes including spontaneous abortion, fetal growth restriction, maternal pathology including hypertensive disorders, or fetal and maternal death. The resolution of inflammation plays an important role throughout pregnancy and is largely mediated by immune cells that produce interleukin (IL)-4 and IL-10. The temporal and spatial aspects of reducing inflammation during pregnancy represent a complex process that if not functioning optimally can lead to persistent inflammation and pregnancy complications. In this review we examine how immune cells that produce IL-4 and IL-10 are regulated throughout pregnancy as well as the effects that reduced IL-4 and IL-10 signaling has on fetal and maternal physiology.